The Influence Of Ambassador Brand, Price And Product Quality On Decisions To Purchase Ms Glow Products In Borobudur - Uswatun Khasanah (MANAGER: Journal of Management and Administration Science, 2024)
This research aims to analyze the influence of brand ambassadorship, price, product quality on purchasing decisions for Ms Glow products. The sample in this study were 37 respondents who had purchased MS Glow products. The data collection technique used was a survey method with the research instrument used was a questionnaire. The results of the instrument test stated that the data in this study was proven to be valid and reliable. In the Classic Assumption Test, it is stated that the data in this study is normally distributed and produces a regression model that is free from multicollinearity, heteroscedasticity, autocorrelation. The results of this research prove that: 1) The R Square value is 0.759. This means that 75.9% of the variations in APBD preparation variables can be explained by the Brand Ambassador, Product Price and Product Quality variables which jointly influence Product Purchasing Decisions. Meanwhile, the remaining 24.1% is explained by other factors outside the model. researched. 2) Partially, the ambassador brand has a significant influence on the decision to purchase Ms Glow products. 3) Partially, product quality has a significant influence on the decision to purchase Ms Glow products. 4) Simultaneously, the ambassador brand and product quality have a significant influence on the decision to purchase Ms Glow products. These results have implications for future researchers to study consumer behavior towards various environmentally friendly toiletry products. The findings of this research have implications for Ms Glow producers to formulate pricing strategies to be able to influence consumer purchasing decisions.